2015
DOI: 10.1128/mcb.01453-14
|View full text |Cite
|
Sign up to set email alerts
|

Rap1 Spatially Controls ArhGAP29 To Inhibit Rho Signaling during Endothelial Barrier Regulation

Abstract: The small GTPase Rap1 controls the actin cytoskeleton by regulating Rho GTPase signaling. We recently established that the Rap1 effectors Radil and Rasip1, together with the Rho GTPase activating protein ArhGAP29, mediate Rap1-induced inhibition of Rho signaling in the processes of epithelial cell spreading and endothelial barrier function. Here, we show that Rap1 induces the independent translocations of Rasip1 and a Radil-ArhGAP29 complex to the plasma membrane. This results in the formation of a multimeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 26 publications
0
88
0
2
Order By: Relevance
“…This study suggested that Rasip1 primarily regulates the integrity of EC-EC adhesions and blood vessel permeability. More recent studies have confirmed aspects of Rasip1 signaling, placing it upstream of Rap1 and cell-cell junctions, but also identifying it as a key regulator of RhoA signaling via Arghap29 in control of the cytoskeleton and cell adhesion [15,16]. Together, these findings underscore the critical importance of Rasip1 for normal morphogenesis of blood vessels and open questions as to how it regulates formation of vessels across diverse vascular beds.…”
Section: Introductionmentioning
confidence: 85%
“…This study suggested that Rasip1 primarily regulates the integrity of EC-EC adhesions and blood vessel permeability. More recent studies have confirmed aspects of Rasip1 signaling, placing it upstream of Rap1 and cell-cell junctions, but also identifying it as a key regulator of RhoA signaling via Arghap29 in control of the cytoskeleton and cell adhesion [15,16]. Together, these findings underscore the critical importance of Rasip1 for normal morphogenesis of blood vessels and open questions as to how it regulates formation of vessels across diverse vascular beds.…”
Section: Introductionmentioning
confidence: 85%
“…Indeed, overexpression of a spontaneously active RhoA leads to a decrease in proplatelets, indicating that RhoA activation inhibits proplatelet formation (28). Of note, it was reported that the Rho signaling pathway could be controlled by the small GTPase Rap1 (40). Interestingly, we have recently demonstrated in VWD-type 2B p.V1316M that the thrombopathy originates from an impaired activation of Rap1 (29).…”
Section: V1316m (2b) Megakaryocytes (Mks)mentioning
confidence: 95%
“…Interestingly, a study by the Bos lab showed that Rap1 activation results in inhibition of RhoA activity, releasing tension from the junction region and thereby promoting stabilization of endothelial cell-cell junctions. [82][83][84] Mechanistically they showed that the adapter protein Ras-interacting protein 1 (Rasip1) is involved in the formation of the endothelial barrier by forming a complex with Rap1 and promoting its activity. 83 This results in the recruitment of ARH-GAP29, a GAP that inactivates RhoA.…”
Section: Endothelial Adherens Junction Control By Rho Gtpasesmentioning
confidence: 99%
“…Thus, by recruiting ARHGAP29, RhoA activity is believed to be locally inhibited, releasing junctional tension and thereby promoting cell-cell junction interaction. 85,86 Endothelial Rho-GEFs and adherens junctions GEFs outnumber their target Rho-GTPase by more than 3-fold. 51 Therefore, different GEFs likely control different pools of the Rho GTPases, which directs local signaling pathways resulting in different outcomes.…”
Section: Endothelial Adherens Junction Control By Rho Gtpasesmentioning
confidence: 99%